Highly Selective Lowpass Filter with Wide Stopband in Suspended Stripline Technology for Millimeter-wave Diplexer Applications - Seyed Milad Miri; Karim Mohammadpour-Aghdam; Seyed Omidreza Miri (AUT Journal of Electrical Engineering)
This paper presents a low loss and high selective lowpass filter which is implemented using suspended stripline (SSL) technology. The proposed structure is comprised of a 13th order generalized Chebyshev lowpass filter which enjoys integrated waveguide-to-SSL transitions. This filter is designed and fabricated to be used as lowpass channel of a U-band diplexer employed in frontend of a U-band down converter. Designed filter has cut-off frequency of 50 GHz with high performance out-of-band rejection and wide stopband associated with stepped-impedance resonators realized using generalized Chebyshev prototype. Final design of filter is analyzed and optimized using 3D full-wave simulator. Filter circuit is realized on one side of a 0.127 mm-thick TLY5 substrate with dielectric constant of 2.2, which is suspended symmetrically in a waveguide channel with height of 0.961 mm and maximum width of 2 mm. Higher order modes propagation effects on filter performance are investigated to have proper single mode operation. In addition, parametric study of SSL is done to predict probable malfunctioning due to misalignment or other fabrication and packaging errors. Measurement results also are presented to verify performance of filter. The filter displays a maximum passband insertion loss of 2 dB and a return loss of better than 10 dB over the passband. Band-edge steepness reaches over 50 dB at 5 GHz away from cut-off and out-of-band rejection is higher than 45 dB at entire stopband, which are in good agreement with simulation.